Kehujjahan Ḥadīth Mawqūf Menurut Muḥaddithīn: Studi Analisis Terhadap Kedudukan Ḥadīth Mawqūf Sebagai Sumber Hukum Islam - Reva Hudan Lisalam (Refleksi: Jurnal Kajian Agama dan Filsafat, 2019)
This article wants to prove that not all the opinions of friends contained in the ḥadīth mawqūf are a compulsory hujjah that must be followed by Muslims afterwards. This is related to the call that arose from some Islamic groups to restore and limit the meaning of the Qur’an and the Prophet’s only in the understanding of generations of friends so that they do not justify the existence of ijtihād on the friend’s ijtihād. This type of research used in this article is library research, namely by inventorying some thoughts about the Hadith Mawquf from the ulama, especially muḥaddithīn because the study of the mawqūf ḥadīth is more deeply discussed in the ḥadīth discipline.